2005
DOI: 10.1111/j.1399-0004.2005.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Frameshift and nonsense mutations in the gene for ATPase7B are associated with severe impairment of copper metabolism and with an early clinical manifestation of Wilson's disease

Abstract: Wilson's disease (WD) is an autosomal recessive disorder of copper metabolism. The clinical phenotype of the disease is varied. It is proposed that this variation may be a result of differential functional disruption of ATPase7B (ATP7B) resulting from mutations in the gene ATP7B. We aimed to assess the relationship between specific mutational defects in ATP7B and divergence in the phenotypic expression of WD. One hundred and forty-two patients with clinically, biochemically and genetically diagnosed WD were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
2
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 33 publications
7
91
2
13
Order By: Relevance
“…Merle et al 11 found that patients with two severe truncating mutations had an onset at 13 years with an interquartile range of 9-13 years, whereas patients with two missense mutations had an onset at 22 years with an interquartile range of 14-27 years. Similar results were published by Gromadzka et al, 38 who reported that in the presence of two severe truncating mutations the age of onset was 14 ± 7 years, while in the presence of two missense mutations the age of onset was 29 ± 9 years. They reported an intermediate age of onset in the presence of one missense mutation and one severe truncating mutation (25±9 years).…”
Section: Severity Of Mutationsupporting
confidence: 80%
See 1 more Smart Citation
“…Merle et al 11 found that patients with two severe truncating mutations had an onset at 13 years with an interquartile range of 9-13 years, whereas patients with two missense mutations had an onset at 22 years with an interquartile range of 14-27 years. Similar results were published by Gromadzka et al, 38 who reported that in the presence of two severe truncating mutations the age of onset was 14 ± 7 years, while in the presence of two missense mutations the age of onset was 29 ± 9 years. They reported an intermediate age of onset in the presence of one missense mutation and one severe truncating mutation (25±9 years).…”
Section: Severity Of Mutationsupporting
confidence: 80%
“…They reported an intermediate age of onset in the presence of one missense mutation and one severe truncating mutation (25±9 years). 38 Interestingly, we found that the p.Q1351X mutation in our material could be classified as moderate with late onset, although it leads to a termination of the protein. Truncating mutations associated with relatively late onset has also been described with p.C271X (age of onset 17-19 years) 39 and p.S932X (age of onset 24 years).…”
Section: Severity Of Mutationmentioning
confidence: 88%
“…19 Patients carrying the R816S(c.2448G4T) mutation had about the same mean age at presentation than p.H1069Q(c.3207C4A) homozygotes (hepatic: 16.3 years; neurological: 23.6 years), with a higher frequency of hepatic presentation. In contrast, patients with truncating 20 or frameshift mutations 21 are associated with early onset of hepatic disease. Thus, like p.H1069Q(c.3207C4A), the R816S(c.2448G4T) mutation might be considered as a 'mild' mutation, although the number of patients is too low to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 96%
“…[20][21][22][23] Furthermore, as reported elsewhere, ceruloplasmin serum levels are also influenced by the ATP7B genotype. 24,25 As for basal daily urinary copper excretion, on the basis of our results, the diagnosis of WD should be considered when this test produces a value > 40 lg/ 24 hours. This cutoff value has also been recently stressed by AASLD guidelines, 2 although its diagnostic Male 60 Neg 121 25 24 1666 ND -NRH ND 2 2 NRH Male 156 Neg 100 23 7 104 ND -NRH ND 0 0 NRH Male 192 Neg 90 22 20 1165 ND -NRH ND 2 2 The WD scores were calculated under the assumption of urinary copper ULNs of **40 and †100 lg/24 hours.…”
Section: Discussionmentioning
confidence: 99%